Attitude towards problem-solving as the effect of problem-posing approach - Agustyani, Anggit Reviana Dewi; Priatna, Nanang; Martadiputra, Bambang Avip Priatna (Department of Mathematics, Universitas Negeri Semarang, 2020)
This study aims to examine whether students’ achievement of attitude towards problem-solving by problem-posing approach better than by direct approach. This study was a quasi-experimental. The population was all students at Junior High School 8 Bandung, 8th-grade for a total of 8 classes, with two classes as the sample. The instrument used to get the data was a questionnaire with five indicators (patience, persistence, perseverance, willingness, and confidence). Data analysis was performed using the t-test and Mann-Whitney U. The results of this study revealed that overall the attitude of students towards problem-solving by problem-posing approach was not significantly better than by direct approach; more specifically, it was equally good, while for each indicator, the result was varied. Moreover, in the class of problem-posing approach, students had patience and persistence in solving problems that were more prominent than aspects of perseverance, willingness, and confidence.